Effects of environmentally friendly agricultural land protection programs: Evidence from the Lake Seyfe area of Turkey - Ismet Boz (Journal of Integrative Agriculture, 2016)
The primary purpose was to investigate the effect of the Environment Friendly Agricultural Land Protection (EFALP) program initiated in 2006. More specifically, the study objectives were to determine the adoption levels of environmentally friendly practices, the extension activities being performed in the region, and to analyse the factors influencing the adoption of the program. Respondents were selected by drawing two stratified samples based on farm size. Cross tabulation and chi-square tests of independence were used to achieve the first objective of the study. Focus-group interviews were conducted for the second objective, and finally, a binary logistic-regression model was applied for the third objective. The findings showed that the adopter farmers used land protection measures extensively relative to the non-adopters, and the Ministry of Food, Agriculture, and Livestock of Turkey, provides useful extension services in the region. Farm size, irrigated land, income level, specialization area, cooperative membership, and travel frequency to large cities influence the adoption of the EFALP program. The conclusion is that the promoted program significantly influenced the protection of the land and other natural resources, and therefore, the regions implementing programs of this type must be extended to other environmentally sensitive areas of the country.